HOTEL PURCHASING SEBAGAI FUNGSI PENGENDALIAN BIAYA DAN PENINGKATAN PROFIT - Hermawan, Budi (Wahana Informasi Pariwisata : MEDIA WISATA, 2003)
Purchasing is a series of activities resulting in the selection and acquisition of desired commodities of services. The purchasing function is extremely important. Any money that is saved during the purchasing process goes directly to bottom line. Purchasing in the hospitality industries operation is a routine activities to purchase the good. Purchasing is an essential activity, because to control the cost of operation could be started from purchase. The wrong purchase cause inefficeintly in operation, and the business could be loss. Managers any business venture must understand the importanceof controlling the purchasing function. Efficiently and effectiveness in purchasing chould be saved cost for product. Its could be to support generating profit in operation. The difficulity generaing a profit is only one of the reasons why the purchasing functionis so pertinent. The purchasing could be efficient and effective if its activity base on 6 (six) objective of purchase, as follows: right product, right price, right quality, right quantity, rigth time and right supplier. Many manager in business has an image that the profit only get from generating sales, to increase the profit, manager must be increase sales of product. However, the purchasing could be generating profit most easily and efficiently more than generating profit from sales. Generating profit in operation could be get from purchasing control. On this manner the business could be increase the power competitive by cost control from purchase.